Manifestasi Klinis dan Neuroimaging pada Reversible Cerebral Vasoconstriction Syndrome (RCVS) - Narithya Julieta, Ni Putu; Pradipta, I Putu Bayu Surya; Kamelia, Luh Putu Lina (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Reversible cerebral vasoconstriction syndrome (RCVS) is a headache with normal cerebrospinal fluid findings, and the angiography shows vasoconstriction with or without focal neurological signs. RCVS will improve spontaneously in 3 months. This condition is more common in women, especially in middle age, but is often underdiagnosed. RCVS has a good prognosis with low recurrence, but complications rarely happen that cause sequelae in patients. Diagnosis is based on clinical symptoms, diagnostic criteria, and radiological features of the patient's cerebral vasculature. Cerebral angiography (DSA) has become the gold standard for RCVS examination. For now, there is no effective therapy in RCVS. Complications that often arise are subarachnoid hemorrhage and ischemic stroke.